Zur statischen Tragfähigkeit geklebter Kreishohlprofilverbindungen im Stahlbau - Albiez, Matthias Friedrich (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2016)
A high capacity adhesively bonded joint of hollow sections in steel construction is developed in the scope of this thesis. In particular, the boundary conditions and requirements of the building industry are considered. The load-bearing behaviour of the adhesively bonded joints is determined and analysed with experimental and numerical investigations. The development and validation of a method to predict the load-bearing capacity of adhesively bonded joints emphasises additional features.